## BRF1011 3 years ago Explain how to solve the equation 3t + 11 = –10. Show that your solution works.

1. Hero

3t + 11 = -10 3t = -21 t = -21/3 t = -7 3(-7) + 11 = -10 -21 + 11 = -10 -10 = -10

2. BRF1011

I'm checkimg my answers on a quiz before I submit it soo dont hate.

3. Hero

lol

4. amistre64

can i despise a little tho?

5. Hero

I wish I had an OS when I was in school.

6. BRF1011

no not even a little. haha

7. amistre64

confound it all!! lol

8. BRF1011

ohh hush hahaha

9. Confucious

First you have to isolate the variable on one side of the equation (or equal sign). You can do this by subtracting 11 from both sides. This will give you the following. \[3t+11=-10\] \[3t=-10-11\] \[3t=-21\]

10. Hero

Equation editor is just too slow for me. I've practically given up on it.

11. HorribleAtMath

well you just get the t to one side, then do simple math from there

12. BRF1011

lol your name "horrible at math" doesnt give you much of a title in this section..you realize that right?? lol

13. HorribleAtMath

Actually, you're question was sort of common sense (things i learned in fifth grade). My username refers to the fact that I am horrible at the math i am doing now (precalculus and ap statistics) were i have A's, but not A pluses.